2018
DOI: 10.1002/bse.2074
|View full text |Cite
|
Sign up to set email alerts
|

Consumer motivations for sustainable consumption: The interaction of gain, normative and hedonic motivations on electric vehicle adoption

Abstract: Recent conceptual studies identify gain, normative and hedonic factors as three categories of motivations of consumer proenvironmental behavior. However, empirical understanding of how these motivations interact and affect proenvironmental behavior is limited. This study is based on a survey of car owners in Sweden (N = 573) and uses structural equation modeling to analyze the data. The empirical findings point to the importance of all three motivations (gain, normative and hedonic) in consumer electric vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
109
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 77 publications
13
109
2
Order By: Relevance
“…The majority of research carried out to date on consumer attitudes towards EM vehicles has focused on people's attitudes towards the environment and barriers to the purchase of EM vehicles [6]. All in all, the findings of this study suggest that the adoption of EM vehicles depends on a wide array of factors (e.g., government incentives and policies, vehicle characteristics, infrastructure availability, price, social and personal issues, environmental concerns) [8][9][10][11][12][13][14][15][16][17]54]. Building on studies related to the adoption of new technologies [33][34][35][36][37], this study is one of a few to investigate consumers' perceived value and its effect on their attitude towards EM vehicles.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The majority of research carried out to date on consumer attitudes towards EM vehicles has focused on people's attitudes towards the environment and barriers to the purchase of EM vehicles [6]. All in all, the findings of this study suggest that the adoption of EM vehicles depends on a wide array of factors (e.g., government incentives and policies, vehicle characteristics, infrastructure availability, price, social and personal issues, environmental concerns) [8][9][10][11][12][13][14][15][16][17]54]. Building on studies related to the adoption of new technologies [33][34][35][36][37], this study is one of a few to investigate consumers' perceived value and its effect on their attitude towards EM vehicles.…”
mentioning
confidence: 73%
“…Nosi [14] posited that the buying intention of EM vehicles was heavily influenced by consumer attitudes and subjective norms, while pre-and post-sale service perception generally had a negative impact. Otherwise, a study by Rezvani et al [15] found that adoption intentions related to EM vehicles were influenced by gain, normative and hedonic motivations. Vehicle leasing was found to be the preferred business model for EM in a study by Liao [16], whereas Rietmann and Lieven [17] found that "the higher the level and amount of political incentives in a country, the higher the country's proportion of EM" (p. 125).…”
Section: Introductionmentioning
confidence: 95%
“…In this regard, the strong influence of an electric mode of drive in our factorial survey is striking. We argue that the relevance of e‐mobility in our study might be on the one hand influenced by potential changes in consumer preferences in the last years (e.g., Rezvani, Jansson, & Bengtsson, ). On the other hand, the preference for electric vehicles might not necessarily or exclusively be an indication for increased environmental awareness but could also positively relate to lifestyle motives when e‐mobility is perceived as an attractive (e.g., sporty, sharp accelerating, and silent) option.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, 75% of respondents strongly expressed the importance of developing environmentally friendly vehicles. Rezvani et al () found that consumers with higher perception regarding the proenvironmental impacts of the EVs have a higher choice probability for EVs. In the previous studies, the environmental attributes were found to have a significant effect on the purchase of EVs, but the estimation results on the relative importance of the environmental attributes to others, such as financial, technical, and infrastructural, were found to vary.…”
Section: Literature Reviewmentioning
confidence: 99%